2009
DOI: 10.4049/jimmunol.0900803
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Function of Bone Marrow-Derived Mesenchymal Stem Cells in Experimental Autoimmune Type 1 Diabetes

Abstract: Human clinical trials in type 1 diabetes (T1D) patients using mesenchymal stem cells (MSC) are presently underway without prior validation in a mouse model for the disease. In response to this void, we characterized bone marrow-derived murine MSC for their ability to modulate immune responses in the context of T1D, as represented in NOD mice. In comparison to NOD mice, BALB/c-MSC mice were found to express higher levels of the negative costimulatory molecule PD-L1 and to promote a shift toward Th2-like respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
302
4
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 348 publications
(327 citation statements)
references
References 50 publications
16
302
4
3
Order By: Relevance
“…However, the immune modulatory function of BM-MSCs has been documented in graftversus-host disease [4][5][6], autoimmune encephalomyelitis [17], sepsis [3], collagen-induced arthritis, and bowel inflammation [15,16,20]. But whether other SC categories have the ability to exert comparable effects was unknown and our results provide novel information supporting the view that a variety of SCs share the critical aspect of being immune privileged.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…However, the immune modulatory function of BM-MSCs has been documented in graftversus-host disease [4][5][6], autoimmune encephalomyelitis [17], sepsis [3], collagen-induced arthritis, and bowel inflammation [15,16,20]. But whether other SC categories have the ability to exert comparable effects was unknown and our results provide novel information supporting the view that a variety of SCs share the critical aspect of being immune privileged.…”
supporting
confidence: 67%
“…Several SC subtypes, including neural SCs [10] and mesenchymal stromal cells (MSCs) [11][12][13][14], possess regenerative potential and may interact with immune effector cells (IECs), profoundly influencing their function in vitro and in vivo. The immune system plays a critical role in the pathogenesis and progression of a number of degenerative diseases, raising the possibility that SCs may be effective in repairing the damaged organ by promoting cell formation and modulating the associated immune response [6,[14][15][16][17][18][19][20]. Based on this premise, the immunogenicity and immune modulatory properties of SCs have to be carefully characterized to decipher their potential clinical import.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] To date, bone marrow-derived MSCs (BM-MSCs) are among the most commonly used MSCs in pre-clinical research for the treatment of rheumatoid arthritis (RA) and other autoimmune diseases. [8][9][10] However, there are some limitations associated with BM-MSCs in clinical applications, including the technical difficulty in acquiring sufficient numbers of cells for therapy. 11 Recently, olfactory ecto-mesenchymal stem cells (OE-MSCs), a new type of resident stem cell in the olfactory lamina propria, have been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that ADSCs would have better clinical applicability, since the neoplasm may occur when using autologous MSCs in NOD mice (33,106). Alternatively, recent reports have highlighted the therapeutic potential of ADSCs for congenital causes or acquired factors of diabetes.…”
Section: Discussion and Future Expectationmentioning
confidence: 99%